Relationship between burnout and empathy in medical students from a private university in Peru - Huarcaya-Victoria, Jeff (2019)
Introduction. Burnout among medical students is a serious and common entity. It has been documented that burnout is related to a reduction in empathy. Objective. To evaluate the relationship between Burnout syndrome and empathy levels in medical students. Methods. A cross-sectional study developed in 245 first year medical students in a medical school from Lima. The Maslach Burnout Inventory-Student Survey (MBISS), the Jefferson Scale of Physician Empathy (JSPE-S) and a sociodemographic data collection sheet were used. Results. It was found that a correlation between the total MBI-SS and the JSPE-S (p = -0,269; p <0,01). The correlations between the dimensions of the burnout and the total of the JSPE-S were: emotional exhaustion (AE) (p = -0,137; p <0,05), cynicism (CI) (p = -0,241; p <0,01) and academic effectiveness (EA) (p = 0,262; p <0,01). Conclusions. Empathy in medical students shows a correlation with all the dimensions of burnout; negatively with the AE and CI, and positively with the EA.